2017
DOI: 10.1111/1365-2435.12890
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology is the primary driver of beak shape diversification in waterfowl

Abstract: Summary The diversity of beak shapes among birds is often assumed to be largely the result of adaptations to different feeding behaviors and diets. However, this assumption has only been tested for a small subset of avian diversity, primarily within the order Passeriformes. Moreover, given the role of the beak in behaviors other than feeding and given that most previously identified beak‐feeding associations concern beak size rather than shape, it remains unclear how much of beak shape diversity is explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
130
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 67 publications
13
130
4
1
Order By: Relevance
“…Our results suggest that dietary transitions toward increased herbivory are correlated with evolutionary changes toward higher anterior MA, implying that herbivory imposes higher performance demands on the beak. This observation is congruent with previous ecomorphological studies on waterfowl (Olsen )…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results suggest that dietary transitions toward increased herbivory are correlated with evolutionary changes toward higher anterior MA, implying that herbivory imposes higher performance demands on the beak. This observation is congruent with previous ecomorphological studies on waterfowl (Olsen )…”
Section: Discussionsupporting
confidence: 93%
“…More nuanced relationships between feeding adaptation and beak shape may be operating, with variable strength, within lower taxonomic levels, to accommodate different macroevolutionary regimes and trade‐offs. For example, while a strong association between feeding ecology and beak shape characterizes the diversification patterns within waterfowl (Olsen ), skull CS, not diet, is a major driver of beak shape in diurnal raptors (Bright et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further benefit of identifying strong links between ecologies and morphologies is that these associations provide critical tools for evolutionary studies, helping researchers to reconstruct paleoecologies of fossil taxa (Meng et al. ; Olsen ; Chen et al. ), examine macroevolutionary patterns in major clades (Grossnickle and Polly ; Mitchell and Makovicky ), and reconstruct paleoenvironments (Vermillion et al.…”
mentioning
confidence: 99%
“…Studies of bird beak shape using discrete categories have not found significant associations between diet and beak shape (e.g., Bright et al. ; Felice and Goswami ) whereas others using more sophisticated representations of diet have (Olsen ). Furthermore, sexual dimorphism in head size has been recorded in at least one species in this study (Badham ; Thompson and Withers ), and it is possible that sex also influences skull shape.…”
Section: Discussionmentioning
confidence: 99%